2006
DOI: 10.1007/s00535-006-1954-3
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection of early gastric cancer

Abstract: The purpose of this review was to examine a remarkable technical advance regarding the indications for and the technique of endoscopic resection of early gastric cancer. Endoscopic mucosal resection (EMR) of early gastric cancer with no risk of lymph node metastasis has been a standard technique in Japan, probably owing to the high incidence of gastric cancer in Japan and the fact that more than half of Japanese gastric cancer cases are diagnosed at an early stage. Very recently, several EMR techniques have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
509
1
19

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 631 publications
(541 citation statements)
references
References 82 publications
12
509
1
19
Order By: Relevance
“…In the study conducted by Miyata et al (32) , a larger lesion size was associated with a higher number of resected fragments, showing a significant difference but no relation to lesion location. Other studies demonstrated a larger lesion size, a lower rate of en bloc resection, even with different techniques and similar local recurrence rates of 1.7% and 2.3%, respectively (11,58) . In this study, all 5 recurrences occurred with lesions smaller than 20 mm, while 3 of them were resected en bloc, so that local recurrence could not be attributed to these risk factors.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the study conducted by Miyata et al (32) , a larger lesion size was associated with a higher number of resected fragments, showing a significant difference but no relation to lesion location. Other studies demonstrated a larger lesion size, a lower rate of en bloc resection, even with different techniques and similar local recurrence rates of 1.7% and 2.3%, respectively (11,58) . In this study, all 5 recurrences occurred with lesions smaller than 20 mm, while 3 of them were resected en bloc, so that local recurrence could not be attributed to these risk factors.…”
Section: Discussionmentioning
confidence: 87%
“…This is the rationale for local resection with endoscopic mucosal resection (EMR), or mucosectomy. The local recurrence rate after EMR for gastric adenocarcinoma ranges from 2% to 35% (11,59) . This is usually minimal for well-differentiated adenocarcinoma: en bloc resected, measuring up to 20 mm in size, restricted to the mucosa, and presenting without ulceration.…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive treatments, including endoscopic mucosal resection (EMR), endoscopic submucosal dissection (ESD) and limited lymphadenectomy, are associated with surgical results that are no worse than those of conventional surgery (Ono et al, 2001). Endoscopic resection is widely performed as an alternative treatment to surgery in patients with mucosal tumors smaller than 20 mm that are of histologically differentiated types without ulceration, which are estimated to carry no risk of lymph node metastasis (Gotoda et al, 2006). In contrast to open procedures, EMR, ESD and limited lymphadenectomy have been performed in recent studies with nearly zero complications.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic mucosal/submucosal resection (EMR) is an effective treatment method for gastric cancer patients. Using EMR, a drug is injected beneath the mucous membrane of a lesion through the endoscopic device, and the mucosa surrounding the lesion is grasped, lifted, strangulated, and resected by electrocautery [3]. Compared with laparotomy, EMR results in an easier recovery, less pain, and a smaller operation wound [4].…”
Section: Introductionmentioning
confidence: 99%